Impact of age on cerebrovascular dilation versus reactivity to hypercapnia. Issue 1 (January 2017) - Coverdale, Nicole S; Badrov, Mark B; Shoemaker, J Kevin
This study quantified the effect of age on cerebrovascular reactivity and cerebrovascular conductance while accounting for differences in grey matter volume in younger (YA: n = 12; 24 ± 4 years, six females) and older adults (OA: n = 10; 66 ± 7 years; five females). Cerebral blood flow velocity (CBFV; transcranial Doppler) in the middle cerebral artery (MCA), MCA cross-sectional area (CSA), intracranial volumes (magnetic resonance imaging), and mean arterial pressure (MAP; Finometer), were measured under normocapnic and hypercapnic (6% carbon dioxide) conditions. Cerebral blood flow (CBF) was quantified from CBFV and MCA CSA and normalized to grey matter volume. Grey matter volume was 719 ± 98 mL in YA and 622 ± 50 mL in OA ( P = 0.009). Cerebrovascular reactivity (%ΔCBF/ΔPET CO2 ) was not different between YA and OA. In contrast, cerebrovascular conductance (CBF/MAP) in response to hypercapnia was reduced in OA ( P = 0.02). Of note, MAP increased more with hypercapnia in OA compared with YA. Therefore, the central hemodynamic response to hypercapnia compensated for a diminished dilatory response downstream from the MCA so that the CBF response to hypercapnia per unit of brain mass was not affected by age. This impairment was not detected by traditional measures of cerebrovascular reactivity.